The Effect of Social Support on Self-Care Behavior of People with Leprosy in Madura Indonesia - Mujib Hannan; Syaifurrahman Hidayat; Emdat Suprayitno; Ratna Indriyani; Angelina da Costa Fernandes (JKG (JURNAL KEPERAWATAN GLOBAL), 2025)
Background: Leprosy has a long-standing history and continues to cause not only health-related complications but also major social difficulties. Individuals affected by this disease require interpersonal support to perform proper self-care and to minimize the risk of further transmission. This research sought to examine the effect of social group support on self-care practices among people with leprosy in Sumenep Regency, Madura, Indonesia. Method: A cross-sectional study was carried out between August and November 2021 in Sumenep Regency. The target population comprised 232 leprosy patients registered at 28 health centers, from which 145 participants were chosen using proportional random sampling. The research instrument was questionnaire covers two main domains: Social Group Support and Self-Care Behavior. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS.  Results: The findings revealed that social group support had a significant impact on self-care behaviors, with a T-value of 6.368 (>1.96). In addition, personal factors also influenced self-care, as indicated by a T-value of 4.110 (>1.96). Conclusion: Both social and personal support significantly enhance self-care behavior in leprosy patients. Strengthening group-based and individual support is therefore essential to improve self-care practices and decrease the likelihood of disease transmission.